Negative electrode and solid lithium-ion secondary battery

JP2026167437APending Publication Date: 2026-10-14HONDA MOTOR CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2025268089
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2025-03-31
Filing Date
2025-12-19
Publication Date
2026-10-14

AI Technical Summary

Benefits of technology

【0025】 本発明によれば、充放電を繰り返しても、反応抵抗の増加率が小さい負極を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2026167437000001_ABST
    Figure 2026167437000001_ABST
Patent Text Reader

Abstract

This provides a negative electrode with a small rate of increase in reaction resistance even after repeated charging and discharging. [Solution] The negative electrode comprises a negative electrode composite layer containing a silicon-based active material 1 and a first solid electrolyte 2. The silicon-based active material 1 is covered by a coating layer 3 containing a second solid electrolyte 31 and a binder 32. At this time, if the nearest region is selected from any 0.20 μm square region attributed to the binder 32 in a 10,000-fold elemental mapping image of the surface of the silicon-based active material 1, the average distance between the regions is between 0.40 μm and 2.00 μm.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a negative electrode and a solid lithium ion secondary battery.

Background Art

[0002] In recent years, research and development on all-solid-state lithium ion secondary batteries that contribute to energy efficiency have been carried out to ensure that more people can access affordable, reliable, sustainable and advanced energy.

[0003] Patent Document 1 describes an all-solid-state battery having a positive electrode layer, a negative electrode layer, and a solid electrolyte layer formed between the positive electrode layer and the negative electrode layer. Here, the negative electrode layer contains a silicon-based active material having an average particle size of less than 2.6 μm, and a first solid electrolyte. Further, a coating layer containing a second solid electrolyte is formed on the surface of the silicon-based active material.

Prior Art Documents

Patent Documents

[0004]

Patent Document 1

Summary of the Invention

Problems to be Solved by the Invention

[0005] However, in the all-solid-state battery described in Patent Document 1, when charge and discharge are repeated, peeling easily occurs at the interface between the first solid electrolyte and the second solid electrolyte contained in the coating layer along with the expansion and contraction of the silicon-based active material, and as a result, the rate of increase in reaction resistance becomes large.

[0006] An object of the present invention is to provide a negative electrode that has a small rate of increase in reaction resistance even after repeated charge and discharge.

Means for Solving the Problems

[0007] (1) A negative electrode comprising a negative electrode composite layer containing a silicon-based active material and a first solid electrolyte, wherein the silicon-based active material is covered by a coating layer containing a second solid electrolyte and a binder, and when the nearest region is selected from an arbitrary 0.20 μm square region attributed to the binder in an elemental mapping image of the surface of the silicon-based active material at 10,000x magnification, the average distance between the regions is 0.40 μm or more and 2.00 μm or less.

[0008] (2) The negative electrode according to (1), wherein the binder is a fluororesin and the elemental mapping image is a fluorine mapping image.

[0009] (3) The negative electrode according to (1) or (2), wherein the negative electrode composite layer has a mass ratio of the binder to the silicon-based active material of 0.01 or more and less than 0.10.

[0010] (4) The negative electrode according to any one of (1) to (3), wherein the negative electrode composite layer has a mass ratio of the second solid electrolyte to the silicon-based active material of 0.01 or more and 0.15 or less.

[0011] (5) The negative electrode according to any one of (1) to (4), wherein the second solid electrolyte is a sulfide solid electrolyte.

[0012] (6) The negative electrode according to (5), wherein the sulfide solid electrolyte is an argyrodite-type sulfide solid electrolyte.

[0013] (7) The negative electrode according to (5) or (6), wherein the first solid electrolyte is the same as the second solid electrolyte.

[0014] (8) The coating layer has a thickness of 1 nm or more and 50 nm or less, and is the negative electrode according to any one of (1) to (7).

[0015] (9) The negative electrode according to (8), wherein the coating layer has a thickness of 2 nm or more and 10 nm or less.

[0016] (10) The coating layer is the negative electrode according to any one of (1) to (9), wherein the binder content is 10% by mass or more and 50% by mass or less.

[0017] (11) The coating layer is the negative electrode according to any one of (1) to (10), wherein the content of the second solid electrolyte is 50% by mass or more and 90% by mass or less.

[0018] (12) The second solid electrolyte is the negative electrode according to any one of (1) to (11), wherein the median diameter is 0.1 μm or more and 1.0 μm or less.

[0019] (13) The negative electrode according to any one of (1) to (12), wherein the negative electrode composite layer has a silicon-based active material content of 50% by mass or more and 90% by mass or less.

[0020] (14) The negative electrode according to any one of (1) to (13), wherein the negative electrode composite layer has a content of the first solid electrolyte of 10% by mass or more and 50% by mass or less.

[0021] (15) The negative electrode according to any one of (1) to (14), wherein the negative electrode composite layer further comprises a second binder.

[0022] (16) The negative electrode according to (15), wherein the negative electrode composite layer contains 1% by mass or more and 10% by mass or less of the second binder.

[0023] (17) A solid lithium-ion secondary battery comprising a negative electrode as described in any one of items (1) to (16).

[0024] A method for manufacturing a negative electrode according to any one of (1) to (16), comprising: a step of mechanically milling the silicon-based active material and the second solid electrolyte to obtain a silicon-based active material coated with a coating layer containing the second solid electrolyte; a step of dry mixing the silicon-based active material coated with the coating layer containing the second solid electrolyte and the binder to obtain a silicon-based active material coated with a coating layer containing the second solid electrolyte and the binder; and a step of applying a slurry containing the silicon-based active material coated with the coating layer containing the second solid electrolyte and the binder, and the first solid electrolyte, to form a negative electrode composite layer. [Effects of the Invention]

[0025] According to the present invention, it is possible to provide a negative electrode in which the rate of increase in reaction resistance is small even after repeated charging and discharging. [Brief explanation of the drawing]

[0026] [Figure 1] This is a cross-sectional view showing a part of the structure of the negative electrode composite layer according to one embodiment of the present invention. [Figure 2] A cross-sectional view showing a part of the structure of the negative electrode composite layer according to a comparative embodiment of the present invention. [Modes for carrying out the invention]

[0027] Embodiments of the present invention will be described below with reference to the drawings.

[0028] [Negative electrode] The negative electrode of this embodiment comprises a negative electrode composite layer containing a silicon-based active material 1 and a first solid electrolyte 2 (see Figure 1). The silicon-based active material 1 is covered by a coating layer 3 containing a second solid electrolyte 31 and a binder 32. When an arbitrary region (A0) of 0.20 μm square, attributed to the binder 32 in a 10,000-fold elemental mapping image of the surface of the silicon-based active material 1, is selected as the nearest region (A1), the average distance between region (A0) and region (A1) is preferably 0.40 μm or more and 2.00 μm or less, preferably 0.42 μm or more and 1.50 μm or less, more preferably 0.46 μm or more and 1.30 μm or less, and even more preferably 0.46 μm or more and 0.60 μm or less. In this case, the distance between region (A0) and region (A1) is the distance between the center of region (A0) and the center of region (A1). Since the average distance between region (A0) and region (A1) is between 0.40 μm and 2.00 μm, even if the silicon-based active material 1 expands and contracts due to repeated charging and discharging, peeling becomes less likely at the interface between the first solid electrolyte 2 and the second solid electrolyte 31 contained in the coating layer 3, and as a result, the rate of increase in reaction resistance becomes smaller.

[0029] In this specification and in the claims, a 0.20 μm square region attributed to binder 32 in a 10,000-fold elemental mapping image of the surface of silicon-based active material 1 means a region selected such that the center of binder 32 is at the center of the region. In this case, the occupancy rate of binder 32 in the region is 50% or more.

[0030] On the other hand, when the silicon-based active material 1 is coated with a coating layer 5 that contains a second solid electrolyte 31 but does not contain a binder 32, instead of the coating layer 3 (see Figure 2), repeated charging and discharging causes the silicon-based active material 1 to expand and contract, making it more prone to delamination at the interface between the first solid electrolyte 2 and the second solid electrolyte contained in the coating layer 5. As a result, the rate of increase in reaction resistance becomes larger.

[0031] Note that instead of the average distance between region (A0) and region (A1), region (A i ) and region (Ai ) and the region closest to it (A i+1 The average distance between regions (A1~A) may be used. In this case, the operation of selecting the nearest region (A1) starting from region (A0), the operation of selecting the nearest region (A2) starting from region (A1), ... is repeated n times to obtain n regions (A1~A) n Select ). n is not particularly limited, but for example, it is an integer greater than or equal to 10.

[0032] The binder 32 is not particularly limited, but examples include styrene-butadiene rubber, fluororesin, and polyimide. Among these, fluororesin is preferred because the binder 32 tends to be scattered. When fluororesin is used as the binder 32, it is preferable to use a fluorine mapping image as the elemental mapping image.

[0033] The fluororesin is not particularly limited as long as it can bond the first solid electrolyte 2 and the second solid electrolyte 31 contained in the coating layer 3, but an example is polyvinylidene fluoride.

[0034] The melt viscosity of binder 32 at 200°C is preferably 20kP or more and 80kP or less, and more preferably 44kP or more and 54kP or less. If the melt viscosity of binder 32 at 200°C is 20kP or more, the rate of increase in reaction resistance will be small even after repeated charging and discharging, and if it is 80kP or less, the initial reaction resistance will be low.

[0035] The mass ratio of binder 32 to silicon-based active material 1 in the negative electrode composite layer is preferably 0.01 or more and less than 0.10, more preferably 0.02 or more and less than 0.07, and even more preferably 0.03 or more and less than 0.05. When the mass ratio of binder 32 to silicon-based active material 1 is 0.01 or more, the rate of increase in reaction resistance is small even after repeated charging and discharging, and when it is less than 0.10, the initial reaction resistance is low.

[0036] The mass ratio of the second solid electrolyte 31 to the silicon-based active material 1 in the negative electrode composite layer is 1% by mass or more and 15% by mass or less.

[0037] The binder 32 content in the coating layer 3 is preferably 10% by mass or more and 50% by mass or less, and more preferably 30% by mass or more and 40% by mass or less. If the binder 32 content in the coating layer 3 is 10% by mass or more, the rate of increase in reaction resistance will be small even after repeated charging and discharging, and if it is 50% by mass or less, the initial reaction resistance will be low.

[0038] The content of the second solid electrolyte 31 in the coating layer 3 is preferably 50% by mass or more and 90% by mass or less, and more preferably 60% by mass or more and 70% by mass or less. When the content of the second solid electrolyte 31 in the coating layer 3 is 50% by mass or more, the initial reaction resistance is low, and when it is 90% by mass or less, the rate of increase in reaction resistance is small even after repeated charging and discharging.

[0039] The thickness of the coating layer 3 is preferably 1 nm or more and 50 nm or less, and more preferably 2 nm or more and 10 nm or less. If the thickness of the coating layer 3 is 1 nm or more, the initial reaction resistance will be low, and if it is 50 nm or less, the rate of increase in reaction resistance will be small even after repeated charging and discharging.

[0040] The silicon-based active material 1 is not particularly limited, but examples include elemental silicon, silicon alloys, silicon oxides, and composite materials containing silicon and other dissimilar elements. Examples of silicon alloys include SiC alloys, SiN alloys, SiTi alloys, SiAl alloys, SiLi alloys, and SiCu alloys. An example of a silicon oxide is SiO. Examples of composite materials containing silicon and other dissimilar elements include silicon-lithium composite materials, silicon-carbon composite materials, and silicon-aluminum composite materials. The composite material containing silicon and other dissimilar elements may be a silicon alloy or not.

[0041] The silicon-based active material 1 is preferably a composite material containing silicon and other dissimilar elements. In a composite material containing silicon and other dissimilar elements, the dissimilar material elements mitigate the effects of the expansion and contraction of silicon during charging and discharging, thus mitigating the volume change of the silicon-based active material 1 due to the expansion and contraction of silicon. As a result, delamination becomes even less likely at the interface between the first solid electrolyte 2 and the second solid electrolyte 31 contained in the coating layer 3, and the rate of increase in reaction resistance becomes even smaller even after repeated charging and discharging.

[0042] The second solid electrolyte 31 is not particularly limited as long as it can conduct lithium ions, but examples include oxide solid electrolytes and sulfide solid electrolytes. Among these, sulfide solid electrolytes are preferred from the viewpoint of initial reaction resistance, and argyrodite-type sulfide solid electrolytes are particularly preferred.

[0043] Sulfide solid electrolytes include, for example, a metal element (M) that acts as a conductive ion and sulfur (S). Examples of M include Li, Na, K, Mg, and Ca. Among these, Li is preferred.

[0044] The sulfide solid electrolyte preferably contains Li, A (one or more elements selected from the group consisting of P, Si, Ge, Al, and B), and S, and more preferably Li and P. Furthermore, the sulfide solid electrolyte may further contain halogen elements (e.g., Cl, Br, I) from the viewpoint of ionic conductivity. The sulfide solid electrolyte may also further contain O.

[0045] Because sulfide solid electrolytes have high ionic conductivity, even if some of the multiple ion conduction paths are interrupted due to repeated charging and discharging, the ionic conductivity is maintained, resulting in a smaller rate of increase in reaction resistance.

[0046] Furthermore, since the sulfide solid electrolyte has high flexibility, even if the volume of the silicon-based active material 1 changes, interfacial peeling and cracking with the first solid electrolyte 2 are less likely to occur. That is, together with the first solid electrolyte 2, it follows the volume change of the silicon-based active material 1, so interfacial peeling and cracking are less likely to occur.

[0047] Examples of the sulfide solid electrolyte include Li2S-P2S5, Li2S-P2S5-LiI, Li2S-P2S5-Li2O, Li2S-P2S5-Li2O-LiI, Li2S-SiS2, Li2S-SiS2-LiI, Li2S-SiS2-LiBr, Li2S-SiS2-LiCl, Li2S-SiS2-B2S3-LiI, Li2S-SiS2-P2S5-LiI, Li2S-B2S3, Li2S-P2S5-Z m S n (where m and n are positive numbers, and Z is Ge, Zn or Ga), Li2S-GeS2, Li2S-SiS2-Li3PO4, Li2S-SiS2-Li x MO y (where x and y are positive numbers, and M is P, Si, Ge, B, Al, Ga or In), Li v P w S x Cl y Br z (v, w, x, y, z>0). Among these, from the viewpoint that the reaction resistance remains low even after repeated charge and discharge, Li v P w S x Cl y Br z (v, w, x, y, z>0) is preferred, and from the viewpoint of ion conductivity, Li v P w S x Cl y Br z (0<v<10, 0<w<5, 0<x<5, 0<y<5, 0<z<5) is more preferred, and examples thereof include Li 5.4 PS 4.4 Cl 0.8 Br 0.8 and the like.

[0048] For example, the description "Li2S-P2S5" refers to a sulfide solid electrolyte made using a raw material composition containing Li2S and P2S5, and the same applies to other descriptions.

[0049] Furthermore, the sulfide solid electrolyte may be sulfide glass or crystalline sulfide glass, or a crystalline material obtained by a solid-phase method. Sulfide glass can be obtained, for example, by performing a mechanical milling method (for example, a method of milling using a ball mill) on the raw material composition. Crystalline sulfide glass can be obtained, for example, by heat-treating sulfide glass at a temperature above its crystallization temperature.

[0050] The median diameter of the second solid electrolyte 31 is preferably 0.1 μm or more and 1.0 μm or less, and more preferably 0.2 μm or more and 0.7 μm or less. When the median diameter of the second solid electrolyte 31 is 0.1 μm or more and 1.0 μm or less, the initial reaction resistance becomes low.

[0051] The first solid electrolyte 2 is the same as the second solid electrolyte 31, but it is preferable that it is identical to the second solid electrolyte 31. This reduces the initial reaction resistance.

[0052] The content of silicon-based active material 1 in the negative electrode composite layer is preferably 50% by mass or more and 90% by mass or less, and more preferably 65% ​​by mass or more and 80% by mass or less. When the content of silicon-based active material in the negative electrode composite layer is 50% by mass or more and 90% by mass or less, the initial reaction resistance becomes low.

[0053] The content of the first solid electrolyte 2 in the negative electrode composite layer is preferably 10% by mass or more and 50% by mass or less, and more preferably 20% by mass or more and 30% by mass or less. When the content of the first solid electrolyte 2 in the negative electrode composite layer is 10% by mass or more and 50% by mass or less, the initial reaction resistance becomes low.

[0054] The negative electrode composite layer preferably further contains a second binder. This reduces the rate of increase in reaction resistance even after repeated charging and discharging.

[0055] The content of the second binder in the negative electrode composite layer is preferably 1% by mass or more and 10% by mass or less, and more preferably 1% by mass or more and 3% by mass or less. If the content of the second binder in the negative electrode composite layer is 1% by mass or more, the rate of increase in reaction resistance will be small even after repeated charging and discharging, and if it is 10% by mass or less, the initial reaction resistance will be low.

[0056] The second binder is similar to binder 32, but preferably identical to binder 32. This reduces the rate of increase in reaction resistance even after repeated charging and discharging.

[0057] The negative electrode composite layer may further contain a conductive additive.

[0058] Conductive additives are not particularly limited, but examples include carbon black such as acetylene black, Ketjen black, channel black, furnace black, lamp black, and thermal black; carbon such as carbon nanotubes and fullerenes; metals such as carbon fluoride, aluminum, and nickel; and conductive polymers such as polyaniline, polythiophene, polyacetylene, and polypyrrole.

[0059] The thickness of the negative electrode composite layer is preferably 0.1 μm or more and 1000 μm or less, more preferably 1 μm or more and 100 μm or less, and even more preferably 10 μm or more and 30 μm or less.

[0060] The negative electrode of this embodiment, for example, has a negative electrode composite material layer formed on a negative electrode current collector, and is applied to a solid lithium-ion secondary battery.

[0061] The materials that make up the negative electrode current collector are not particularly limited, but examples include silver, palladium, gold, platinum, aluminum, copper, nickel, stainless steel, and carbon. Among these, copper, stainless steel, and nickel are preferred from the viewpoint of conductivity and cost.

[0062] The shape of the negative electrode current collector is not particularly limited, but examples include foil-like, plate-like, mesh-like, non-woven fabric-like, and foam-like forms.

[0063] The thickness of the negative electrode current collector is not particularly limited, but for example, it is between 0.1 μm and 1 mm.

[0064] [Method for manufacturing a negative electrode] The method for manufacturing the negative electrode of this embodiment includes the step of mechanically milling the silicon-based active material 1 and the second solid electrolyte 31 to obtain the silicon-based active material 1 coated with a coating layer containing the second solid electrolyte 31. When mechanically milling the silicon-based active material 1 and the second solid electrolyte 31, for example, a ball mill is used. At this time, before mechanically milling the silicon-based active material 1 and the second solid electrolyte 31, the silicon-based active material 1 and the second solid electrolyte 31 may be pre-ground using, for example, a mortar and pestle.

[0065] The method for manufacturing the negative electrode of this embodiment further includes a step of dry mixing a silicon-based active material 1 coated with a coating layer containing a second solid electrolyte 31 and a binder 32 to obtain a silicon-based active material 1 coated with a coating layer 3 containing a second solid electrolyte 31 and a binder 32. This allows the binder 32 to be scattered on the surface of the silicon-based active material 1 coated with a coating layer containing a second solid electrolyte 31. When dry mixing the silicon-based active material 1 coated with a coating layer containing a second solid electrolyte 31 and the binder 32, for example, a rotation-revolution mixer is used.

[0066] The method for manufacturing the negative electrode of this embodiment further includes the step of applying a slurry containing a silicon-based active material 1, which is covered by a coating layer 3 containing a second solid electrolyte 31 and a binder 32, and a first solid electrolyte, to form a negative electrode composite layer.

[0067] The slurry may contain a solvent with a boiling point of 120°C or higher.

[0068] Solvents with a boiling point of 120°C or higher are not particularly limited, but examples include butyl butyrate (boiling point 166°C), o-xylene (boiling point 144°C), m-xylene (boiling point 139°C), p-xylene (boiling point 138°C), and decane (boiling point 174°C).

[0069] [Solid-state lithium-ion rechargeable battery] The solid lithium-ion secondary battery of this embodiment includes the negative electrode of this embodiment, but further comprises, for example, a positive electrode and an electrolyte. The solid lithium-ion secondary battery is not particularly limited, but examples include an all-solid-state lithium-ion secondary battery with a solid electrolyte and a semi-solid-state lithium-ion secondary battery with a gel electrolyte. The all-solid-state lithium-ion secondary battery will be described below.

[0070] (solid electrolyte layer) The solid electrolyte constituting the solid electrolyte layer is not particularly limited, but examples include sulfide solid electrolytes and oxide solid electrolytes. Among these, sulfide solid electrolytes are preferred from the viewpoint of initial reaction resistance, and argyrodite-type sulfide solid electrolytes are particularly preferred.

[0071] The form of the solid electrolyte is not particularly limited, but for example, particles can be used.

[0072] The solid electrolyte content in the solid electrolyte layer is not particularly limited, but is, for example, 50% by mass or more and 99% by mass or less.

[0073] The solid electrolyte layer may further contain a binder or the like.

[0074] The method for forming the solid electrolyte layer is not particularly limited, but one example is a method of applying a slurry containing a solid electrolyte.

[0075] The thickness of the solid electrolyte layer may be between 0.1 μm and 1000 μm.

[0076] (positive electrode) For example, the positive electrode has a positive electrode composite layer formed on the positive electrode current collector.

[0077] The positive electrode composite layer contains a positive electrode active material. The positive electrode active material is not particularly limited, but examples include lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), and LiNi p Mn q Co r O2(p+q+r=1), LiNi p Al q Co r O2 (p+q+r=1), lithium manganese (LiMn2O4), Li 1+x Mn 2-x-y M y Examples include O4(x+y=2) (where M is one or more elements selected from the group consisting of Al, Mg, Co, Fe, Ni, and Zn), lithium titanate, and LiMPO4 (where M is one or more elements selected from the group consisting of Fe, Mn, Co, and Ni).

[0078] The content of positive electrode active material in the positive electrode composite layer may be 20% by mass or more, 40% by mass or more, or 50% by mass or more. On the other hand, the content of positive electrode active material in the positive electrode composite layer may be 99% by mass or less, 90% by mass or less, 80% by mass or less, or 60% by mass or less.

[0079] The positive electrode composite layer may further contain a solid electrolyte. The solid electrolyte is not particularly limited as long as it is capable of conducting lithium ions, but examples include oxide solid electrolytes and sulfide solid electrolytes. Among these, sulfide solid electrolytes are preferred from the viewpoint of initial reaction resistance, and argyrodite-type sulfide solid electrolytes are particularly preferred.

[0080] The positive electrode composite layer may further contain a binder, a conductive additive, and the like.

[0081] The method for forming the positive electrode composite layer is not particularly limited, but one example is a method of applying a slurry containing the positive electrode active material.

[0082] The materials used to constitute the positive electrode current collector are not particularly limited, but examples include aluminum, aluminum alloys, stainless steel, nickel, iron, and titanium. Among these, aluminum, aluminum alloys, and stainless steel are preferred.

[0083] The shape of the positive electrode current collector is not particularly limited, but examples include foil-shaped and plate-shaped.

[0084] Although embodiments of the present invention have been described above, the present invention is not limited to the above embodiments, and the above embodiments may be modified as appropriate within the scope of the spirit of the present invention. [Examples]

[0085] The following describes embodiments of the present invention, but the present invention is not limited to these embodiments.

[0086] [Example 1] (Manufacturing of solid electrolytes) Li2S, P2S5, LiCl, and LiBr 5.4 PS 4.4 Cl 0.8 Br 0.8 After weighing to meet the required composition, the mixture was mixed in an agate mortar for 5 minutes. 2 g of the resulting mixture was placed in a container of a planetary ball mill, followed by the addition of dehydrated heptane and ZrO2 balls, and the container was completely sealed. The container was mounted in the planetary ball mill and mechanically milled at a disc rotation speed of 500 rpm for 20 hours. The mixture was then dried at 110°C for 1 hour to remove the heptane and obtain a coarse-grained material.

[0087] The coarse-grained material was granulated. Specifically, the coarse-grained material was mixed with dehydrated heptane and dibutyl ether, and adjusted to a total volume of 10 g and a solid content concentration of 10% by mass. The resulting mixture was placed in a container of a planetary ball mill, then ZrO2 balls were added, and the container was completely sealed. The container was mounted on the planetary ball mill, and mechanical milling was performed at a base plate rotation speed of 150 rpm. After that, it was dried, and the median diameter (D50 ) 700nm argyrodite-type sulfide solid electrolyte (Li 5.4 PS 4.4 Cl 0.8 Br 0.8 ) was obtained.

[0088] (Formation of the coating layer) Using a mortar, 92 parts by mass of silicon / carbon composite material and median diameter (D 50 ) 700nm argyrodite-type sulfide solid electrolyte (Li 5.4 PS 4.4 Cl 0.8 Br 0.8 )8 parts by mass were dry-kneaded to obtain a preliminary pulverized material. Next, the preliminary pulverized material was mechanically milled using a planetary ball mill and 5 mm diameter zirconia balls to form a coating layer containing a sulfide solid electrolyte on the surface of the silicon / carbon composite material.

[0089] Using a rotation-revolution mixer, 95 parts by mass of a silicon / carbon composite material coated with a sulfide solid electrolyte and 5 parts by mass of polyvinylidene fluoride (PVDF) with a melt viscosity of 50 kP at 200°C were dry-mixed to form a coating layer containing the sulfide solid electrolyte and PVDF by dotting the PVDF on the surface of the silicon / carbon composite material coated with the sulfide solid electrolyte. At this time, the thickness of the coating layer was 0.01 μm.

[0090] Using a scanning electron microscope-energy dispersive X-ray spectrometer (SEM-EDX), a fluorine mapping image at 10,000x magnification was obtained from the surface of a silicon / carbon composite material coated with a coating layer containing a sulfide solid electrolyte and PVDF. Starting from any region with a major axis of 0.2 μm or more that was attributed to PVDF in the fluorine mapping image, the operation of selecting the nearest region was repeated nine times to select 10 regions. After selecting 10 regions, the average distance between the nearest regions (PVDF dossiness) was calculated to be 0.45 μm. At this time, using the image analysis software ImageJ, green regions with a contrast value range of 40 to 255 in the fluorine mapping image were attributed to PVDF.

[0091] (Manufacturing of negative electrodes) Using an ultrasonic homogenizer, 70 parts by mass of silicon / carbon composite material coated with a coating layer containing a sulfide solid electrolyte and PVDF, with a median diameter (D 50 ) 700nm argyrodite-type sulfide solid electrolyte (Li 5.4 PS 4.4 Cl 0.8 Br 0.8 27 parts by mass of ), 2 parts by mass of polyvinylidene fluoride (PVDF), and 1 part by mass of the conductive additive acetylene black Li-100 (manufactured by Denka) were dispersed in butyl butyrate to obtain a slurry.

[0092] After applying the slurry to the copper foil and drying it to form a negative electrode composite layer, the layer was punched out to a diameter of 10 mm to obtain the negative electrode.

[0093] [Example 2] In the formation of the coating layer, a negative electrode was obtained in the same manner as in Example 1, except that 97 parts by mass of silicon / carbon composite material coated with a sulfide solid electrolyte and 3 parts by mass of PVDF were dry-mixed. At this time, the coating layer had a thickness of 0.01 μm and the PVDF dosing density was 0.48 μm.

[0094] [Example 3] In the formation of the coating layer, a negative electrode was obtained in the same manner as in Example 1, except that 99 parts by mass of silicon / carbon composite material coated with a sulfide solid electrolyte and 1 part by mass of PVDF were dry-mixed. At this time, the coating layer had a thickness of 0.01 μm and the PVDF dosing density was 1.22 μm.

[0095] [Comparative Example 1] In the formation of the coating layer, the silicon / carbon composite material coated with a sulfide solid electrolyte and the PVDF were not dry-mixed, except that the negative electrode was obtained in the same manner as in Example 1.

[0096] [Comparative Example 2] In the formation of the coating layer, a negative electrode was obtained in the same manner as in Example 1, except that 90 parts by mass of silicon / carbon composite material coated with a sulfide solid electrolyte and 10 parts by mass of PVDF were dry-mixed. At this time, the coating layer had a thickness of 0.01 μm and the PVDF dispersion was 0.37 μm.

[0097] [Example 4] (Manufacturing of solid electrolytes) Except for changing the mechanical milling time, the median diameter (D) was the same as in Example 1. 50 ) 200 nm argyrodite-type sulfide solid electrolyte (Li 5.4 PS 4.4 Cl 0.8 Br 0.8 ) was obtained.

[0098] (Formation of the coating layer) Using a mortar, 92 parts by mass of silicon / carbon composite material and median diameter (D 50 ) 200 nm argyrodite-type sulfide solid electrolyte (Li 5.4 PS 4.4 Cl 0.8 Br 0.8 )8 parts by mass were dry-kneaded to obtain a preliminary pulverized material. Next, the preliminary pulverized material was mechanically milled using a planetary ball mill and 5 mm diameter zirconia balls to form a coating layer containing a sulfide solid electrolyte on the surface of the silicon / carbon composite material.

[0099] Using a rotation-revolution mixer, 95 parts by mass of a silicon / carbon composite material coated with a sulfide solid electrolyte and 5 parts by mass of polyvinylidene fluoride (PVDF) with a melt viscosity of 50 kP at 200°C were dry-mixed to form a coating layer containing the sulfide solid electrolyte and PVDF by dotting the PVDF on the surface of the silicon / carbon composite material coated with the sulfide solid electrolyte. At this time, the thickness of the coating layer was 0.01 μm.

[0100] Using a scanning electron microscope-energy dispersive X-ray spectrometer (SEM-EDX), a fluorine mapping image at 10,000x magnification was obtained from the surface of a silicon / carbon composite material coated with a coating layer containing a sulfide solid electrolyte and PVDF. Starting from any region with a major axis of 0.2 μm or more that was attributed to PVDF in the fluorine mapping image, the operation of selecting the nearest region was repeated nine times to select 10 regions. After selecting 10 regions, the average distance between the nearest regions (PVDF dossiness) was calculated to be 0.45 μm. At this time, using the image analysis software ImageJ, green regions with a contrast value range of 40 to 255 in the fluorine mapping image were attributed to PVDF.

[0101] (Manufacturing of negative electrodes) Using an ultrasonic homogenizer, 67.5 parts by mass of silicon / carbon composite material coated with a coating layer containing a sulfide solid electrolyte and PVDF, with a median diameter (D) was obtained. 50 ) 200 nm argyrodite-type sulfide solid electrolyte (Li 5.4 PS 4.4 Cl 0.8 Br 0.8 30.5 parts by mass of ), 1 part by mass of polyvinylidene fluoride (PVDF), and 1 part by mass of the conductive additive acetylene black Li-100 (manufactured by Denka) were dispersed in butyl butyrate to obtain a slurry.

[0102] After applying the slurry to the copper foil and drying it to form a negative electrode composite layer, the layer was punched out to a diameter of 10 mm to obtain the negative electrode.

[0103] [Example 5] In the formation of the coating layer, a negative electrode was obtained in the same manner as in Example 4, except that 97 parts by mass of silicon / carbon composite material coated with a sulfide solid electrolyte and 3 parts by mass of PVDF were dry-mixed. At this time, the coating layer had a thickness of 0.01 μm and the PVDF dispersion was 0.48 μm.

[0104] [Example 6] In the formation of the coating layer, a negative electrode was obtained in the same manner as in Example 4, except that 99 parts by mass of a silicon / carbon composite material coated with a sulfide solid electrolyte and 1 part by mass of PVDF were dry-mixed. At this time, the coating layer had a thickness of 0.01 μm and the PVDF dispersion was 1.22 μm.

[0105] [Comparative Example 3] In the formation of the coating layer, the silicon / carbon composite material coated with a sulfide solid electrolyte and the PVDF were not dry-mixed, except that the negative electrode was obtained in the same manner as in Example 4.

[0106] [Comparative Example 4] In the formation of the coating layer, a negative electrode was obtained in the same manner as in Example 4, except that 90 parts by mass of a silicon / carbon composite material coated with a sulfide solid electrolyte and 10 parts by mass of PVDF were dry-mixed. At this time, the coating layer had a thickness of 0.01 μm and the PVDF dispersion was 0.37 μm.

[0107] [Half-cell manufacturing] Median diameter (D 50 ) 700nm argyrodite-type sulfide solid electrolyte (Li 5.4 PS 4.4 Cl 0.8 Br 0.8 After placing the material into a 10mm diameter zirconia cylindrical tube, it is clamped with a SUS jig and processed at 2t / cm 2 It was pressed to obtain a solid electrolyte layer. Next, the solid electrolyte layer and the negative electrode were stacked at 10 t / cm². 2 The solid electrolyte layer-anode laminate was pressed to obtain a solid electrolyte layer-anode laminate. Next, the solid electrolyte layer-anode laminate was restrained with a restraining pressure of 3 MPa and left in a vacuum environment at 200°C for 2 hours. Then, a 10 mm diameter lithium foil was laminated on the solid electrolyte layer side of the solid electrolyte layer-anode laminate and restrained with a restraining pressure of 3 MPa to obtain a half cell.

[0108] [Charge / Discharge Test] A charge-discharge test was conducted on a half-cell. Specifically, the battery was charged and discharged three times at a constant current density of 0.1C within the voltage range corresponding to 0% to 60% of the state of charge (SOC) at 25°C. The charge-discharge test was stopped at 60% SOC during the first and third cycles, and the AC impedance was measured. The reaction resistance R1 [Ω·cm] at 60% SOC during the first charge-discharge cycle was measured. 2 ] and the reaction resistance R3 [Ω·cm] at SOC 60% during the third charge / discharge cycle. 2 After measuring [the value], the rate of increase in reaction resistance R3 / R1 was calculated.

[0109] [Dispersion state of PVDF at the negative electrode] Using a scanning electron microscope-energy dispersive X-ray spectrometer (SEM-EDX), a fluorine mapping image at 1000x magnification of the cross-section of the negative electrode was acquired to evaluate the dispersion state of PVDF. The criteria for determining the dispersion state of PVDF are as follows: A: If there are no regions with a diameter of 3.5 μm or more. B: If there is a region with a diameter of 3.5 μm or more

[0110] Tables 1 and 2 show the evaluation results for half-cells.

[0111] [Table 1]

[0112] [Table 2]

[0113] Tables 1 and 2 show that when using the negative electrodes of Examples 1 and 4-6, the rate of increase in reaction resistance is small even after repeated charging and discharging. This is presumed to be because the PVDF dispersion state is good in the negative electrode, resulting in a smaller rate of increase in reaction resistance. Furthermore, when using the negative electrodes of Examples 2 and 3, it is presumed that the rate of increase in reaction resistance will be small even after repeated charging and discharging, similar to the case where the negative electrode of Example 1, which has a good PVDF dispersion state, is used.

[0114] In contrast, in Comparative Examples 1 and 3, the negative electrodes lack PVDF on the surface of the silicon / carbon composite material, resulting in a large increase in reaction resistance with repeated charging and discharging. Similarly, in Comparative Example 4, the PVDF dispersion is poor, leading to a large increase in reaction resistance with repeated charging and discharging. Furthermore, in Comparative Example 2, the PVDF dispersion is also poor, which is likely to result in a large increase in reaction resistance with repeated charging and discharging. [Explanation of Symbols]

[0115] 1. Silicon-based active material 2 First solid electrolyte 3, 5 Covering layer 31 Second solid electrolyte 32 Binders

Claims

1. The negative electrode composite layer comprises a silicon-based active material and a first solid electrolyte, The silicon-based active material is coated with a coating layer containing a second solid electrolyte and a binder. A negative electrode in which, starting from an arbitrary 0.20 μm square region attributed to the binder in an elemental mapping image of the surface of the silicon-based active material at 10,000x magnification, the nearest region is selected, and the average distance between the regions is between 0.40 μm and 2.00 μm.

2. The binder is a fluororesin, The negative electrode according to claim 1, wherein the elemental mapping image is a fluorine mapping image.

3. The negative electrode according to claim 1 or 2, wherein the negative electrode composite layer has a mass ratio of the binder to the silicon-based active material of 0.01 or more and less than 0.

10.

4. The negative electrode according to claim 1 or 2, wherein the negative electrode composite layer has a mass ratio of the second solid electrolyte to the silicon-based active material of 0.01 or more and 0.15 or less.

5. The negative electrode according to claim 1 or 2, wherein the second solid electrolyte is a sulfide solid electrolyte.

6. The negative electrode according to claim 5, wherein the sulfide solid electrolyte is an argyrodite-type sulfide solid electrolyte.

7. The negative electrode according to claim 5, wherein the first solid electrolyte is the same as the second solid electrolyte.

8. The negative electrode according to claim 1 or 2, wherein the coating layer has a thickness of 1 nm or more and 50 nm or less.

9. The negative electrode according to claim 8, wherein the coating layer has a thickness of 2 nm or more and 10 nm or less.

10. The negative electrode according to claim 1 or 2, wherein the coating layer contains 10% by mass or more and 50% by mass or less of the binder.

11. The negative electrode according to claim 1 or 2, wherein the coating layer contains 50% by mass or more and 90% by mass or less of the second solid electrolyte.

12. The negative electrode according to claim 1 or 2, wherein the second solid electrolyte has a median diameter of 0.1 μm or more and 1.0 μm or less.

13. The negative electrode according to claim 1 or 2, wherein the negative electrode composite layer contains 50% by mass or more and 90% by mass or less of the silicon-based active material.

14. The negative electrode according to claim 1 or 2, wherein the negative electrode composite layer contains 10% by mass or more and 50% by mass or less of the first solid electrolyte.

15. The negative electrode according to claim 1 or 2, wherein the negative electrode composite layer further comprises a second binder.

16. The negative electrode according to claim 15, wherein the negative electrode composite layer contains 1% by mass or more and 10% by mass or less of the second binder.

17. A solid lithium-ion secondary battery comprising the negative electrode described in claim 1 or 2.

18. A method for manufacturing a negative electrode according to claim 1 or 2, The process involves mechanically milling the silicon-based active material and the second solid electrolyte to obtain a silicon-based active material coated with a coating layer containing the second solid electrolyte, A step of dry mixing a silicon-based active material coated with a coating layer containing the second solid electrolyte and the binder to obtain a silicon-based active material coated with a coating layer containing the second solid electrolyte and the binder, A method for manufacturing a negative electrode, comprising the steps of applying a slurry containing a silicon-based active material coated with a coating layer containing the second solid electrolyte and the binder, and a first solid electrolyte, to form a negative electrode composite layer.

Citation Information

Patent Citations

  • All-solid battery and manufacturing method thereof

    JP2020021674A